2023
DOI: 10.3390/toxics11090784
|View full text |Cite
|
Sign up to set email alerts
|

Nootkatone Mitigated Melamine-Evoked Hepatotoxicity by Featuring Oxidative Stress and Inflammation Interconnected Mechanisms: In Vivo and In Silico Approaches

Ola Habotta,
Ahmed Abdeen,
Ali Roomi
et al.

Abstract: Melamine (ML) is a common environmental contaminant, commonly used in food fraud, representing a serious health hazard and jeopardizing human and animal health. Recently, nootkatone (NK), a naturally occurring sesquiterpenoid, has garnered considerable attention due to its potential therapeutic advantages. We investigated the potential mechanisms underlying the protective effects of NK against ML-induced liver injury in rats. Five groups were utilized: control, ML, NK10, ML-NK5, and ML-NK10. ML induced substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Increased NF-κB expression levels in hepatocytes of MM-exposed rats was observed which indicated that inflammatory reaction mediated by MM exposure. 58 In addition, MM induced oxidative and inflammatory stresses in macrophages and human embryonic kidney cells by activating the NF-κB/COX-2 and NOX/ROS pathways, besides increasing prostaglandin E2 production. 44 Therefore, a marked alteration in the inflammatory, and antioxidant markers in MM-intoxicated group might be attributed to the production of calcium oxalate crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Increased NF-κB expression levels in hepatocytes of MM-exposed rats was observed which indicated that inflammatory reaction mediated by MM exposure. 58 In addition, MM induced oxidative and inflammatory stresses in macrophages and human embryonic kidney cells by activating the NF-κB/COX-2 and NOX/ROS pathways, besides increasing prostaglandin E2 production. 44 Therefore, a marked alteration in the inflammatory, and antioxidant markers in MM-intoxicated group might be attributed to the production of calcium oxalate crystals.…”
Section: Discussionmentioning
confidence: 99%
“…PMT/vPvM substances can be found in a wide range of applications and sources, including in industrial processes, fire-fighting foams, and consumer products such as food, cosmetics and furniture [15]. They can cause long-term harm to humans and the environment and are also costly and difficult to remove from drinking water [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…PMT/vPvM substances can be found in a wide range of applications and sources, including in industrial processes, fire-fighting foams, and consumer products such as food, cosmetics and furniture [14]. They can cause longterm harm to humans and the environment and are also costly and difficult to remove from drinking water [15][16][17][18]. PMT/vPvM substances have been suggested to have an equivalent level of concern as persistent, bioaccumulative and toxic (PBT) substances or very persistent and very bioaccumulative (vPvB) substances.…”
Section: Introductionmentioning
confidence: 99%